Cross-Protective Immunity to Leishmania amazonensis is Mediated by CD4+ and CD8+ Epitopes of Leishmania donovani Nucleoside Hydrolase Terminal Domains - Nico, Dirlei; Gomes, Daniele Crespo; Alves-Silva, Marcus Vinícius; Freitas, Elisangela Oliveira; Morrot, Alexandre; Bahia, Diana; Palatnik, Marcos; Rodrigues, Mauricio M.; Palatnik-de-Sousa, Clarisa B. (Frontiers in Immunology, 2014)
The nucleoside hydrolase (NH) of Leishmania donovani (NH36) is a phylogenetic marker of high homology among Leishmania parasites. In mice and dog vaccination, NH36 induces a CD4+ T cell-driven protective response against Leishmania chagasi infection directed against its C-terminal domain (F3). The C-terminal and N-terminal domain vaccines also decreased the footpad lesion caused by Leishmania amazonensis. We studied the basis of the crossed immune response using recombinant generated peptides covering the whole NH36 sequence and saponin for mice prophylaxis against L. amazonensis. The F1 (amino acids 1–103) and F3 peptide (amino acids 199–314) vaccines enhanced the IgG and IgG2a anti-NH36 antibodies to similar levels. The F3 vaccine induced the strongest DTH response, the highest proportions of NH36-specific CD4+ and CD8+ T cells after challenge and the highest expression of IFN-γ and TNF-α. The F1 vaccine, on the other hand, induced a weaker but significant DTH response and a mild enhancement of IFN-γ and TNF-α levels. The in vivo depletion with anti-CD4 or CD8 monoclonal antibodies disclosed that cross-protection against L. amazonensis infection was mediated by a CD4+ T cell response directed against the C-terminal domain (75% of reduction of the size of footpad lesion) followed by a CD8+ T cell response against the N-terminal domain of NH36 (57% of reduction of footpad lesions). Both vaccines were capable of inducing long-term cross-immunity. The amino acid sequence of NH36 showed 93% identity to the sequence of the NH A34480 of L. amazonensis, which also showed the presence of completely conserved predicted epitopes for CD4+ and CD8+ T cells in F1 domain, and of CD4+ epitopes differing by a single amino acid, in F1 and F3 domains. The identification of the C-terminal and N-terminal domains as the targets of the immune response to NH36 in the model of L. amazonensis infection represents a basis for the rationale development of a bivalent vaccine against leishmaniasis.